2007
DOI: 10.1080/07036330701442315
|View full text |Cite
|
Sign up to set email alerts
|

‘Bridging the Gap’ between EU Politics and Citizens? The European Commission, National Media and EU Affairs in the Public Sphere

Abstract: Information about political processes is an important prerequisite for debates in the public sphere, which can strengthen the legitimacy of decisions. This article analyses how far both Commission communication and media news coverage contain information on (a) policy issues, (b) the policy process and (c) the actors involved and the positions they take. Data have been gathered through a qualitative content analysis of Commission communication output and the news coverage in two Dutch and two German newspapers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
0
22
0
3
Order By: Relevance
“…Posle proširenja Evropske unije 2004. godine, ali i u kasnijim godinama, kada su opstanak zajedničke valute, jedinstvenog tržišta i celog "evropskog projekta" dovedeni u pitanje zbog posledica svetske ekonomske krize, medijski prostor posvećen problemima i izazovima na nadnacionalnom nivou ostao je skučen. Pristup medija u izveštavanju o EU u tim turbulentnim periodima nije više bio isključivo negativan, ali se pokazao površnim i nacionalno fokusiranim (Bijsmans & Altides, 2007;Esser et al, 2012;Price, 2002;Trenz, 2004).…”
Section: Uvodunclassified
See 2 more Smart Citations
“…Posle proširenja Evropske unije 2004. godine, ali i u kasnijim godinama, kada su opstanak zajedničke valute, jedinstvenog tržišta i celog "evropskog projekta" dovedeni u pitanje zbog posledica svetske ekonomske krize, medijski prostor posvećen problemima i izazovima na nadnacionalnom nivou ostao je skučen. Pristup medija u izveštavanju o EU u tim turbulentnim periodima nije više bio isključivo negativan, ali se pokazao površnim i nacionalno fokusiranim (Bijsmans & Altides, 2007;Esser et al, 2012;Price, 2002;Trenz, 2004).…”
Section: Uvodunclassified
“…Novinari često ne razumeju komplikovane i nedovoljno transparentne procedure donošenja odluka u glavnim političkim institucijama EU o kojima izveštavaju (Bijsmans & Altides, 2007;Meyer, 1999). Na medijsko izveštavanje o EU utiču i drugi faktori, kao što su politički sistem jedne zemlje i dominacija proevropskih ili evroskeptičnih političkih snaga, zatim uređivačka politika medijske kuće, ali i "novinarski napor koji se ulaže u pokrivanje događaja ili teme, izvori finansiranja, istraživanje i primena kriterijuma selekcije vesti" (de Vreese, 2001: 287).…”
Section: Teorijski Okvirunclassified
See 1 more Smart Citation
“…The previous discussion focuses on a sample of (English language) newspapers from across the world and considers the total level of coverage of business ethics. Authors such as Bijsmans and Altides (2007) and Brossard et al (2004) have noted regional differences in the coverage of the same ethical issues. Rossouw (2002) also suggests that different parts of the world consider business ethics differently, suggesting that African businesses do not consider ethics to be an integral part of what they do.…”
Section: Contextualising Business Ethics From a Regional Perspectivementioning
confidence: 99%
“…Early work on EU correspondents (Morgan 1995) raised very important points with regards to the access, constraints, and sources defining EU news stories (see also de Vreese 2003b). The question of the Living Reviews in European Governance http://www.livingreviews.org/lreg-2007-3 relationship between EU institutions and journalists (Bijsmans and Altides 2007;Martins et al 2012;Meyer 1999;Morgan 1995) remains center-place, and a series of studies have addressed the role of journalism in the European integration trajectory (Baisnée 2002;Balčytienė and Vinciūnienė 2010;Gleissner and de Vreese 2005;Statham 2008Statham , 2010Lecheler 2008). In a recent overview, Statham (2010) concluded that journalists still find the EU to be a difficult topic to cover and to entice editors and audiences about.…”
Section: Living Reviews In European Governancementioning
confidence: 99%